2020
DOI: 10.1186/s40780-020-00168-6
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen gargle for chemo- or Chemoradiotherapy-induced Oral Mucositis: a feasibility study

Abstract: Background: Oral mucositis frequently occurs in cancer patients treated with chemotherapy and chemoradiotherapy (CRT). This study examined the safety and efficacy of ibuprofen gargle in healthy volunteers and patients with chemotherapy-and concomitant CRT-induced oral mucositis. Methods: We enrolled healthy volunteers and patients with chemotherapy-and CRT-induced oral mucositis. In cohort I, single and multiple doses of ibuprofen gargle (0.6% or 1.0%) were administered to healthy volunteers on day 1 and days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…In a previous report on healthy subjects and patients with chemotherapy/chemoradiotherapy-associated oral mucositis [19], the mean ΔVAS and ΔVAS standard deviation (SD) of pain relief after 3 days of use were -1.28 and 0.84 (n = 7 patients), respectively, of which the pre-use VAS value of ibuprofen gargle was more than 3. In the subgroup with a VAS of 3 or more before ibuprofen gargle use, the ΔVAS was -1.56 and the ΔSD was 0.81 (n = 5).…”
Section: Sample Size Calculationmentioning
confidence: 86%
See 2 more Smart Citations
“…In a previous report on healthy subjects and patients with chemotherapy/chemoradiotherapy-associated oral mucositis [19], the mean ΔVAS and ΔVAS standard deviation (SD) of pain relief after 3 days of use were -1.28 and 0.84 (n = 7 patients), respectively, of which the pre-use VAS value of ibuprofen gargle was more than 3. In the subgroup with a VAS of 3 or more before ibuprofen gargle use, the ΔVAS was -1.56 and the ΔSD was 0.81 (n = 5).…”
Section: Sample Size Calculationmentioning
confidence: 86%
“…We have reported that there were no major safety concerns and that some pain relief was obtained with an ibuprofen gargle in patients with chemo-or chemoradiotherapy-induced oral mucositis [19]. Ibuprofen gargles are retained in the mouth for about 1 minute and then spat out, so it is unlikely that ibuprofen will be absorbed into the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that an oral gargle containing dissolved ibuprofen (0.6% or 1%) delivered directly to the affected area could contribute to pain relief for oral mucositis. In our previous study, we have reported that there are no major safety concerns and that some pain relief is obtained for chemotherapy- or chemoradiotherapy-associated oral mucositis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is hoped that ibuprofen-containing gargles will provide an efficient drug delivery system targeting the painful area after tooth extraction, with minimal systemic effects. An unresolved limitation of our previous study [ 25 ] is that it was not possible to estimate the extent to which a placebo effect may have been present because the study was an uncontrolled trial involving healthy adults and patients with chemotherapy- or chemoradiotherapy-associated oral mucositis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%